2004
DOI: 10.1002/jmv.20170
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis C virus in Iran as reflected by phylogenetic analysis of the NS5B region

Abstract: Hepatitis C virus (HCV) subtypes were determined in 125 Iranian patients by phylogenetic analysis within the NS5B or 5'-UTR/core regions. Subtypes 1a and 3a were predominant accounting for 47 and 36%, whereas 1b and 4 accounted for 8 and 7%. This subtype distribution differs from that of Turkey and Pakistan, where subtypes 1b and 3a dominate and also from neighbouring Arabic countries where subtype 4 is the prevalent genotype. The Iranian 1a and 3a strains formed subclusters in the dendrogram indicating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
45
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 27 publications
(26 reference statements)
18
45
2
Order By: Relevance
“…This is in accordance with Zali et al's study, the first study on prevalence of HCV genotyping from Iranian population, conducted on Tehran haemodialysis patients [8]. Later, Samimi-Rad et al, in a survey on Iranian anti-HCV positive patients from Tehran and 5 other cities of the country, showed that genotype 1a was predominant (47%) and genotypes 3a, 1b and 4 were detected in 36%, 8% and 7% of the patients respectively [10]. In another study at 45 haemodialysis centres of Tehran, Hosseini-Moghaddam et al revealed that 3a (30.3%) and 1a (28.8%) were the most prevalent genotypes, and 1b, 3b and 4 accounted for 18.2%, 3.0%, and 16.7% respectively [9].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This is in accordance with Zali et al's study, the first study on prevalence of HCV genotyping from Iranian population, conducted on Tehran haemodialysis patients [8]. Later, Samimi-Rad et al, in a survey on Iranian anti-HCV positive patients from Tehran and 5 other cities of the country, showed that genotype 1a was predominant (47%) and genotypes 3a, 1b and 4 were detected in 36%, 8% and 7% of the patients respectively [10]. In another study at 45 haemodialysis centres of Tehran, Hosseini-Moghaddam et al revealed that 3a (30.3%) and 1a (28.8%) were the most prevalent genotypes, and 1b, 3b and 4 accounted for 18.2%, 3.0%, and 16.7% respectively [9].…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies from Islamic Republic of Iran have shown that genotypes 1a and 3a are the most common genotypes in our country [6,[8][9][10]. This is different from the dominant genotypes of other countries in the Eastern Mediterranean region [6,11,12].…”
Section: Introductionmentioning
confidence: 84%
“…One patient was with genotype 4 [11]. The results of other studies on circulating HCV genotypes in the Iranian patients showed that genotypes 1a,3a and 1b are predominant respectively and that type 4 is rare [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Turkey serves as a bridge between Europe and Asia, and HCV genotype pattern is similar to Eastern and Southern European countries, having genotype 1b as the most frequent genotype (> 70%) followed by genotype 1a [62] . HCV genotype 3a is the most common subtype in Iran followed by genotype 1a, 1b and 4 [63] . The predominant genotypes (1a and 4) are the most difficult-to-treat groups.…”
Section: Chronic Hepatitis Cmentioning
confidence: 99%